2002
DOI: 10.1002/asi.10120
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating community information seeking using the Internet: Findings from three public library–community network systems

Abstract: We report findings from a recent study of how public libraries are using on-line community networks to facilitate the public's information seeking and use in everyday situations. These networks have been lauded for their potential to strengthen physical communities through increasing information flow about local services and events, and through facilitating civic interaction. However, little is known about how the public uses such digital services and what barriers they encounter. This article presents finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…These alternative and often affective ways in which people benefit from information were documented further by such researchers as Harris and Dewdney (1994) who studied battered women, by Chatman (cf. 2000) in her series of ethnographic studies on different fringe populations, Pettigrew, Durrance, and Unruh (2002) in their investigation of how people use the Internet for situations of daily living, and by Pettigrew (2000) when she addressed information flow among nurses and the elderly at community clinics. Pettigrew, for example, found that instead of acting directly upon referrals provided by nurses to attain services, seniors said they used and thus benefited from nurses' information in simply knowing that help was available if needed, that someone was concerned for them, and that alternative ways of solving their problem could be derived from the nurses' referrals.…”
Section: In Their Seminal 1977 Work Public Library Use Users Uses:mentioning
confidence: 99%
“…These alternative and often affective ways in which people benefit from information were documented further by such researchers as Harris and Dewdney (1994) who studied battered women, by Chatman (cf. 2000) in her series of ethnographic studies on different fringe populations, Pettigrew, Durrance, and Unruh (2002) in their investigation of how people use the Internet for situations of daily living, and by Pettigrew (2000) when she addressed information flow among nurses and the elderly at community clinics. Pettigrew, for example, found that instead of acting directly upon referrals provided by nurses to attain services, seniors said they used and thus benefited from nurses' information in simply knowing that help was available if needed, that someone was concerned for them, and that alternative ways of solving their problem could be derived from the nurses' referrals.…”
Section: In Their Seminal 1977 Work Public Library Use Users Uses:mentioning
confidence: 99%
“…Research on the information-seeking behavior of low-income people (Chatman, 1991;Spink & Cole, 2001) and research in the vein of Dervin's sensemaking approach (Dervin, 1992) have done much to expand the contexts in which studies are undertaken. Other promising arenas for expansion include studies of the role of community information systems in helping individuals and building communities (Pettigrew, Durrance, & Unruh, 2002) and the role of the Internet in everyday life information seeking (Rieh). A recent article by Kari and Hartel (2007) calls for more studies of information behavior in leisure activities.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1970s, the first community network made computer terminals available in different places within a city so that community members could share or find local data in an electronic bulletin board [11]. This attempt was later followed by discussion forums [28], question and answers sites [2], local email lists or listservs [9,15] and websites that provided an integrated view of local information [9,27]. Regardless of the specific technology, community networks often obtained their content from residents of the the local communities [2,11,9,17,25,27].…”
Section: Information Systems For Local Communitiesmentioning
confidence: 99%